Comparative study of water and energy use in selected automobile manufacturing industries. (10th February 2020) - Babel, Mukand S.; Oo, Eaindra; Shinde, Victor R.; Kamalamma, Ambili G.; Haarstrick, Andreas
Abstract: Industries are striving to become more efficient in using water resources and energy, both of which are rapidly becoming scarce. The automobile sector, the highest emitter of CO2 into the atmosphere, is under pressure to reduce the emissions it creates in the various stages of its products' life cycle. This study attempted to analyze and quantify the use of water and energy in five automobile manufacturing industries namely BMW, Daimler, FCA, Nissan and Volkswagen. Additionally, the study also explored the potential for reducing CO2 emissions in these industries by bringing down its water and energy consumption. On an average, 4.94 m 3 of water and 2.74 MW h of energy are used directly to produce a car. Among the companies analyzed, BMW is highly water efficient and generates more revenue out of one unit of energy consumed. Other companies are also achieving their own efficiency targets by employing several resource efficient technologies. The analysis shows that both water and energy use must be reduced to have a substantial reduction in CO2 emission. BMW needs to reduce its water use by 38% and energy consumption by 31% to have a 15% reduction in CO2 emission. Nissan has the highest potential to reduce CO2 emissions by reducing its water use and energy consumption. Minimizing the use of resources, coupled with switching to renewable resources, could bring about emission reductions in the industry to a larger extent. Highlights: Water and energy use and carbon emissions are compared among 5 automotive companies. 4.94 m 3 of water and 2.74 MW h of energy are used directly in vehicle production. BMW is most water efficient and generates more revenue per unit of energy consumed. Carbon emission reduction potential by reducing water and energy uses was examined.